Agribusiness startup among agricultural students: awareness, perception, constraints and students’ expectations from the university - Balaji, S; Malarkodi, M; Uma, K; Padma, S R; Soundararajan, R P (Plant Science Today, 2025)
This study empirically examines how graduate students’ awareness and perception of agribusiness startups influence their intention to start an agribusiness startup, focusing on those factors based on the theory of planned behaviour. To know the constraints that reduce the entrepreneurial intention among the students and their expectations from the university. The study employed a purposive sampling design, involving 211 students from the Agricultural University, Coimbatore. In India, startups have rapidly emerged as the third-largest startup ecosystem in the world, following the USA and China. The results of the study revealed that students possess moderate awareness about agribusiness startups, with an average mean score of 3.64 and entrepreneurial intention was positively influenced by a favourable perception of agribusiness and university support. Major constraints identified that unfair competition from larger market players, with a Garrett mean score of 58.72 and a lack of equity capital Garrett mean score of 58.16, these barriers significantly reduced the confidence and interest of students in starting agribusiness ventures. Students emphasized the need for mentorship programs, interaction with successful agripreneurs and entrepreneurship education as key expectations from their university. The findings suggest that strengthening university support systems and addressing financial barriers could enhance student participation in agribusiness startups.